2014
DOI: 10.14694/edbook_am.2014.34.e397
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the Treatment of Locally Advanced and Metastatic Squamous Cell Carcinoma of the Skin: A Rising Unmet Need

Abstract: Squamous cell carcinoma of the skin (SCCS) is a common malignancy with potentially devastating consequences in patients with locally advanced or metastatic disease. Its rising incidence, primarily a result of an aging population and increased ultraviolet (UV) radiation exposure, characterize an emerging unmet need. A firm understanding of the biology of this disease, likely distinct from that of other squamous malignancies because of the influence of UV radiation, is necessary in the evaluation of treatment pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…7 Given this rising burden of disease and the limited systemic therapeutic options for advanced cSCC, novel treatment options such as immune checkpoint inhibitors need to be explored. 8 A recent meta-analysis demonstrated that immunohistochemical expression of PD-L1 in tumor cells was associated with clinical response to PD-1/PD-L1 inhibitors in metastatic melanoma and non-squamous NSCLC but not in renal cell carcinoma or squamous NSCLC. Clinical and follow up data:…”
mentioning
confidence: 99%
“…7 Given this rising burden of disease and the limited systemic therapeutic options for advanced cSCC, novel treatment options such as immune checkpoint inhibitors need to be explored. 8 A recent meta-analysis demonstrated that immunohistochemical expression of PD-L1 in tumor cells was associated with clinical response to PD-1/PD-L1 inhibitors in metastatic melanoma and non-squamous NSCLC but not in renal cell carcinoma or squamous NSCLC. Clinical and follow up data:…”
mentioning
confidence: 99%
“…While there are various treatment options for localized NMSCs, for example surgery, radiotherapy and topical treatment, management of advanced or metastatic NMSCs remains difficult. Single‐agent or combination chemotherapy regimens, as well as antibodies targeting epidermal growth factor receptor, may be used in the treatment of advanced or metastatic SCC . However, the duration of response to the often toxic treatment regimens is limited in most patients.…”
mentioning
confidence: 99%
“…Mutation and hypermethylation can inactivate CDKN2A, which may be responsible for the development of SCC (Figure 1) [5].…”
Section: Cdkn2amentioning
confidence: 99%
“…Some studies have reported theincidence of SCC of the skin, in up to 4-31% of those individuals, who were taking Vemurafenib, Dabrafenib and Sorafenib. BRAF-inhibitors may cause mutation in RAS by paradoxical activation of the MAPK pathway ( Figure 1) [5].…”
Section: Rasmentioning
confidence: 99%
See 1 more Smart Citation